Lactic Acid Fermentation Improved Textural Behaviour, Phenolic Compounds and Antioxidant Activity of Chia ( Salvia hispanica L.) Dough - Bustos, Ana Yanina; Gerez, Carla Luciana; Mohtar Mohtar, Lina Goumana; Paz Zanini, Verónica Irene; Nazareno, Mónica Azucena; Taranto, María Pía; Iturriaga, Laura Beatriz (Food technology and biotechnology, 2017)
In this work, autochthonous lactic acid bacteria (LAB) were isolated from chia ( L.) dough and selected on the basis of the kinetics of acidification and proteolytic activity. Strain no. C8, identified as C8, was selected and used as starter to obtain chia sourdough. Lactic acid fermentation increased the organic acid mass fractions (lactic, acetic and phenyl lactic acids to 12.3 g, 1.0 g and 23.8 µg per kg of dough respectively), and antioxidant activities, which increased by approx. 33-40% compared to unfermented chia flour dough. In addition, total phenolic content increased 25% and its composition was strongly modified after 24 h of fermentation by C8. Chlorogenic acid was only found in the fermented dough (2.5 mg/g), while ferulic acid was detected from the beginning of fermentation, being 32% higher in chia sourdough (5.6 mg/g). The use of fermented chia sourdough improved the overall characteristics of white bread, including physical ( reduced hardness and chewiness of the crumb) and antioxidant properties (25% on average), compared to the white bread. These results indicate that the use of chia sourdough could be a promising alternative to improve the technological and antioxidant properties of wheat bread. In addition, this work has shown, for the first time, that lactic acid bacterium is able to ferment chia dough, improving its overall characteristics.